The Influence of ICT Application on Students' Level of Understanding and Mastery of Physics: Pengaruh Penerapan ICT Dalam Tingkat Pemahaan Dan Penguasaan Fisika Pada Mahasiswa - Syifa, Aliyya Layyinatu; Munthe, Clara Dwipuan; Setiaji, Bayu (Borneo Educational Journal (Borju), 2024)
This research aims to determine the influence of Information and Communication Technology (ICT) on students' understanding of physics learning, aimed at students majoring in Physics Education, Yogyakarta State University, Class of 2023. In this research, data collection was obtained from distributing questionnaires to students of Physics Education, UNY 2023. Results data This research was processed using parametric statistical methods. The supporting applications used are Excel to tabulate data and SPSS which is used to analyze data obtained from research results. There are several stages carried out in parametric data processing, namely, normality test, linearity test, and t-test. In the normality test, a significance value of 0.200 was obtained. In the linearity test, the Sig value was obtained. deviation from linearity is 0.930. Then the t-test obtained a significance value of 0.001. It can be concluded from the results of the three tests and based on the basis for decision-making, that the research data is normally distributed, the variables are interconnected and influence each other.